2018
DOI: 10.1021/acs.inorgchem.8b01253
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroism in Iron-Based Oxyfluoride Perovskites

Abstract: Multiferroic materials with simultaneous magnetic and ferroelectric ordering that persist above room temperature are rare. Using first-principles density functional theory calculations, we demonstrate fluorination of oxygen-deficient AA'FeO perovskites, where A and A' are cations with +3 and +2 oxidation states, respectively, and have a layered ordering, as an effective strategy to obtain room-temperature multiferroics. We show that by controlling the size of the A and A' cations, it is possible to stabilize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Besides, stabilization of Fe 3+ within the structure can provide strong superexchange interactions to sustain magnetic ordering above room temperature, as for instance in YBaFe 2 O 5 , 21 YFeO 3 , 22 and LaCa 2 Fe 3 O 8 . 23 The combination of these properties of iron can result in multiferroism, as it has been recently suggested for the layered perovskite YCaFe 2 O 5 F. 17 First-principle density functional theory calculations support strong polarization and robust magnetic ordering above room temperature in YCaFe 2 O 5 F; besides, the possibility of preparing this material by a layer-by-layer growth technique capable of imposing Y and Ca ordering has been suggested.…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Besides, stabilization of Fe 3+ within the structure can provide strong superexchange interactions to sustain magnetic ordering above room temperature, as for instance in YBaFe 2 O 5 , 21 YFeO 3 , 22 and LaCa 2 Fe 3 O 8 . 23 The combination of these properties of iron can result in multiferroism, as it has been recently suggested for the layered perovskite YCaFe 2 O 5 F. 17 First-principle density functional theory calculations support strong polarization and robust magnetic ordering above room temperature in YCaFe 2 O 5 F; besides, the possibility of preparing this material by a layer-by-layer growth technique capable of imposing Y and Ca ordering has been suggested.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Despite this, there are ways to combine magnetism and ferroelectricity in perovskites such as BiFeO 3 , in which magnetic ordering is associated with Fe, but the Bi lone-pair is responsible for the ferroelectric behavior . Although ferromagnetism is usually the type of magnetic ordering occurring in magnetoelectric–multiferroic perovskites, the combination of ferroelectricity and antiferromagnetism has been predicted in the orthorhombic BaMnO 3 and in YCaFe 2 O 5 F . Layered-type ordering of different A-cations coupled with particular octahedral tilting systems of the anion sublattice results in non-centrosymmetric polar perovskites. , A more recent approach consisting of the combination of cation ordering with anion-vacancy ordering to generate polar structures has been demonstrated on epitaxially grown SrFeO 2.5 /CaFeO 2.5 thin-film superlattices .…”
Section: Introductionmentioning
confidence: 99%
“…This is probably derived from lower electron density of Mn–O bonds in MnTaO 2 N than that in MnTiO 3 due to higher electronegativity of the O 2– ions as compared to the N 3– ions. Positive correlation between J parameter and covalency has recently been confirmed in oxyfluorides; the superexchange interaction is suppressed by substituting F for O due to the less covalency of metal–F bonds than metal–O bonds. …”
Section: Resultsmentioning
confidence: 95%
“…This observation ultimately led to the conclusion that (NH 4 ) 3 MoO 3 F 3 exhibited a distorted crystal structure, and the oxide and fluoride ions formed a solid solution. Since then, oxyfluoride perovskites have remained of keen interest for their peculiar crystal chemistry and prospect for noncentrosymmetry. Investigations that followed ultimately revealed that the [MO x F 6– x ] n– heteroleptic units in these perovskites exhibit local anion order. Weak interactions, however, among neighboring anionic groups led to long-range orientational disorder.…”
Section: Introductionmentioning
confidence: 99%